Men's Help-Seeking for Depression: Attitudinal and Structural Barriers in Symptomatic Men - Simon M. Rice; John L. Oliffe; David Kealy; Zac E. Seidler; John S. Ogrodniczuk (SAGE Publishing, 2020)
Objective: Men with depression are known to have significant challenges with health service engagement. The current study sought to better understand attitudinal and structural mental health care barriers among those men identified as symptomatic for symptoms of major depression. Design: Cross-sectional study with data provided by Canadian men via a nationally representative online survey. Outcomes examined depression, suicide risk, and barriers to mental health services. Participants: A total of 117 men (mean age = 42.36 years) reporting symptoms of major depression consistent with moderate severity as identified by the Patient Health Questionnaire-Depression Module (PHQ-9). Results: In all, 51.3% of the sample reported previously receiving counselling or psychotherapy for mental health concerns. The majority (63.2%) reported past 2-week suicide or self-harm ideation; however, only a small proportion (8.5%) were currently engaged with professional mental health support. Logistic regression indicated that men's attitudinal barriers to mental health help-seeking had a greater predictive effect than structural barriers (33% vs 0% of items, respectively). In particular, lower likelihood of help-seeking was associated with men's reluctance to disclose mood-related symptoms to their physician/family doctor (adjusted odds ratio [AOR] = 0.37), a tendency for self-reliance and solving one's own problems (AOR = 0.34), and uncertainly about the process of psychotherapy (AOR = 0.29). Conclusion: Gender-transformative approaches to primary health care may be key to improving men's rates of disclosure and increasing detection for depression and suicide risk.